2021
DOI: 10.1371/journal.pone.0250730
|View full text |Cite
|
Sign up to set email alerts
|

Utility of hospitalization for elderly individuals affected by COVID-19

Abstract: Background During the COVID-19 pandemic, the number of individuals needing hospital admission has sometimes exceeded the availability of hospital beds. Since hospitalization can have detrimental effects on older individuals, preference has been given to younger patients. The aim of this study was to assess the utility of hospitalization for elderly affected by COVID-19. We hypothesized that their mortality decreases when there is greater access to hospitals. Methods This study examined 1902 COVID-19 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…We observed that the admission of patients with a Charlson index of more than 2 reduced over time because of the related observed reduction in comorbid burden in the whole cohort [ 11 , 15 , 17 ]. Nevertheless, in the third wave, we observed a reduced hospitalization of patients with many comorbid conditions in accordance with recent evidence that older patients could be treated safely at home or in nursing homes [ 30 ] but also for the possible effect of prioritizing vaccination to frail patients. Moreover, this latter effect is likely the cause of the strong reduction in SARS-CoV-2 infections observed in subjects more than 85 years old and in patients with dementia.…”
Section: Discussionsupporting
confidence: 90%
“…We observed that the admission of patients with a Charlson index of more than 2 reduced over time because of the related observed reduction in comorbid burden in the whole cohort [ 11 , 15 , 17 ]. Nevertheless, in the third wave, we observed a reduced hospitalization of patients with many comorbid conditions in accordance with recent evidence that older patients could be treated safely at home or in nursing homes [ 30 ] but also for the possible effect of prioritizing vaccination to frail patients. Moreover, this latter effect is likely the cause of the strong reduction in SARS-CoV-2 infections observed in subjects more than 85 years old and in patients with dementia.…”
Section: Discussionsupporting
confidence: 90%
“…24 Studies in most countries showed a significant decrease in the use of different health services during the COVID-19 pandemic. [24][25][26][27][28][29][30][31][32][33][34] Sing and colleagues conducted a qualitative study to examine community perceptions of COVID-19 and their experiences towards health services utilization during the pandemic in Nepal. Their study showed that some factors such as public fear and anxiety of COVID-19, transportation disruptions, unavailability T A B L E 1 Demographic and socioeconomic profile of participants and their association with service utilization pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Such automatized digital health solutions allow real-time 24/7 health monitoring of patients, prioritizing medical treatment according to the patients' health conditions, reducing medical appointments in clinics and hospitals, by sharing secure information among healthcare professionals. This is especially of interest when treating the elderly, as they are at greater risk in hospital environments as concluded in Costantino et al (2021). Therefore, the framework presented in this paper can enable fewer hospital admissions of elderly people while closely monitoring their health and prioritizing more severe cases.…”
Section: Introductionmentioning
confidence: 98%